2015
DOI: 10.5653/cerm.2015.42.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Artificial oocyte activation in intracytoplasmic sperm injection cycles using testicular sperm in humanin vitrofertilization

Abstract: ObjectiveArtificial oocyte activation (AOA) is an effective method to avoid total fertilization failure in human in vitro fertilization-embryo transfer (IVF-ET) cycles. AOA performed using a calcium ionophore can induce calcium oscillation in oocytes and initiate the fertilization process. We evaluated the usefulness of AOA with a calcium ionophore in cases of total fertilization failure in previous cycles and in cases of severe male factor infertility patients with non-motile spermatozoa after pentoxifylline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Similarly, Kovacic et al reported that if immotile sperm in TESE tissue were cultured with pentoxifylline for 20 min, 97% of them started to move; hence, vital spermatozoa could be distinguished more easily, the procedure was shortened, and the fertilization rates and numbers of embryos increased [ 55 ]. The use of pentoxifylline to stimulate sperm motility in fresh or frozen/thawed suspensions has also been reported in other studies [ 56 , 57 , 58 ]. Since the cAMP level in spermatozoa with normal motility is sufficiently high to activate the subsequent cascades, PDE inhibitors have the most pronounced effect on sperm with poor motility [ 59 ].…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsisupporting
confidence: 54%
“…Similarly, Kovacic et al reported that if immotile sperm in TESE tissue were cultured with pentoxifylline for 20 min, 97% of them started to move; hence, vital spermatozoa could be distinguished more easily, the procedure was shortened, and the fertilization rates and numbers of embryos increased [ 55 ]. The use of pentoxifylline to stimulate sperm motility in fresh or frozen/thawed suspensions has also been reported in other studies [ 56 , 57 , 58 ]. Since the cAMP level in spermatozoa with normal motility is sufficiently high to activate the subsequent cascades, PDE inhibitors have the most pronounced effect on sperm with poor motility [ 59 ].…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsisupporting
confidence: 54%
“…The use of calcium ionophore A23187 has been found to salvage oocyte activation failure cases, leading to pregnancies in cycles with diminished oocyte reserves [24], although this is still a matter of discussion [25]. Delivery of healthy babies has been reported in severe male factor IVF cycles [18][19][20][26][27][28] and in normozoospermic IVF cycles [21]. Furthermore, A23187 treatment improved embryo development and IVF outcome in couples with embryos showing developmental problems in previous IVF attempts [29].…”
Section: Introductionmentioning
confidence: 99%
“…In challenging cases where the issues arising reflect problems on both the oocyte and the sperm the technique of artificial oocyte activation (AOA) in conjunction with methylxanthines treatment has been shown to ensure fertilization. However, it seems that the results are mostly attributed to the AOA rather than the actual use of methylxanthines treatment [Kang et al 2015].…”
Section: Methylxanthines: Pentoxifylline and Theophyllinementioning
confidence: 95%